Mount Hope landscape - unknown:::Creator::::::::::::
A photo of the land near which Grosssteinbecks and Dicksons settled in 1854, probably near what was called by westerners 'Mount Hope.' The Grosssteinbecks had purchased 3 hectares of arboreal land and a house in this area in 1853. Digital copy only. No hard copy.